THE ADMISSIBILITY OF CRIMINAL CONVICTIONS IN CIVIL PROCEEDINGS - koh beng, oh you; a/l Thiagarajan , Shanmugam; Nuriskandar, Lalu Hendri (STIS Darussalam Bermi, 2022)
Admissibility of criminal convictions as evidence in criminal proceedings has become a controversial decision of the Court of Appeal of United Kingdom in the case of Hollington v Hewthorn (1943). Since then several follow-up decisions has either adopted this decision and some jurisdictions have rejected it. This article assesses the effect of this decision in four jurisdictions, i.e UK, Australia, Canada and Malaysia. It is found that UK, Australia and Canada have since moved away from this judgement by amendment to their respective Evidence Acts. However, this is not so in the case of Malaysia. This paper recommends that Malaysia revisit section 43 of the Evidence Act 1950 with a view to amend this section to be on par with UK, Australia and Canada.